Impact of different parametric Patlak imaging approaches and comparison with a 2-tissue compartment pharmacokinetic model with a long axial field-of-view (LAFOV) PET/CT in oncological patients - Pan, Leyun; Sachpekidis, Christos; Hassel, Jessica C.; Christopoulos, Petros; Dimitrakopoulou-Strauss, Antonia (European journal of nuclear medicine and molecular imaging, 2025)
The recently introduced Long-Axial-Field-of-View (LAFOV) PET-CT scanners allow for the first-time whole-body dynamic- and parametric imaging. Primary aim of this study was the comparison of direct and indirect Patlak imaging as well as the comparison of different time frames for Patlak calculation with the LAFOV PET-CT in oncological patients. Secondary aims of the study were lesion detectability and comparison of Patlak analysis with a two-tissue-compartment model (2TCM).
Gesehen am 17.02.2025